Water resources management and planning under climate uncertainty: assessment of the droughts in Uzbekistan - Abdullaev, Iskandar; Gafurov, Zafar; Kenjabaev, Shavkat (2025)
Uzbekistan, a predominantly arid country in Central Asia, is highly vulnerable to recurrent droughts that threaten agriculture, water security, ecosystems, and socio-economic stability. Irrigation from the Amu Darya and Syr Darya sustains over 85% of cultivated land, making the economy one of the most irrigation-dependent globally. Past droughts, notably the 1999–2001 event, exposed systemic weaknesses in centralized water allocation, outdated infrastructure, and limited institutional capacity. Economic losses from droughts already reach hundreds of millions annually and are projected to escalate to USD 5 billion per year, about 3% of GDP, by 2050 without adaptation. Climate change will intensify risks, with temperatures expected to rise 4–6°C by 2100 and crop yields declining up to 60% for wheat per 1°C increase.